The Willingness of Motivations to Fund The Visual Game Project: A Case Study in Crowdfunding From Visual Novel Game – Xagia Wars - Atik Aprianingsih; Teresia Debby; Iqro Setiawan Jati; Ira Fachira (School of Business, IPB University (SB-IPB), 2022)
Nowadays, crowdfunding is an alternative way to find funds to develop a product or service. It is no exception for game creators who want to get funds to develop the games they will create. This study is unique and was made based on a case study of Xagia Wars, a visual game created by a game creator in Jakarta called Vifth Floor. This study analyzes the motivations to increase a funder's willingness to fund a visual game project. This study used observation and netnography to get data and regression analysis to measure the motivation to fund the visual game project. The results showed that the factors that influence the funders' willingness to fund are the level of innovation of the project, reward, involvement, and support for the project. Several things need to be considered for project creators to increase the rate of successful crowdfunding. Such as the value of the reward, whether it makes people interested, a visual game must-have innovation, and invite the funders to participate in the game creation process so that funders can provide support for what is needed is not only in the form of funds. Keywords: crowd-funding, funding, game, visual novel game